Hypoxanthine-Guanine Phosphoribosyltransferase Variant Associated with Accelerated Purine Synthesis - Benke, Paul J. (1973)
We have previously described a 14-yr-old boy with hyperuricemia, renal failure, and accelerated purine production resistant in vivo and in vitro to purine analogs. This patient demonstrated normal red cell hypoxanthine-guanine phosphoribosyltransferase (HPRT) heat stability, electrophoresis at high pH, and activity at standard substrate levels. In the present report an abnormal HPRT enzyme was demonstrated by enzyme kinetic study with phosphoribosylpyrophosphate (PRPP) as the variable substrate and inhibitory studies with sodium fluoride. Apparently normal HPRT activity in a patient with hyperuricemia and gout does not exclude a functionally significant HPRT mutation.